SUKSESI JENIS TUMBUHAN PADA AREAL BEKAS KEBAKARAN HUTAN RAWA GAMBUT - Aciana, .; Astiani, Dwi; Burhanuddin, . (JURNAL HUTAN LESTARI, 2017)
This study aims to obtain information on the post-fire natural succession of plants peatland, which can be obtained from the composition of plant species. Data of existing after burning plant species composition can be measured from trees that are still alive on peatland which could be useful for the purposes of restoration on peatlands. This research was conducted at the area of ex-burnt peat swamp forest in 2014 and 2009 at Kuala Dua Village, Sungai Raya District, Kubu Raya Regency, Jully-August 2016. The method used in this research was survey method with purposive multiple plot samples observation. In the sample plots, vegetation analysis was performed. The results showed that in the ex-burnt area of 2014, there were 10 plants species consisting of the ground storey, sapling, the pole and the tree level i.e., jagu, paku-pakuan, resam (Dicranopteris linearis), kemunting , medang (Litsea grandis), kalimutu (Trema orientalis), asam rawa, jering hutan (Acrhidendron ellipticum), mahang and meranti (Shorea sp). Whereas in 2009 found 8 types of plants such as paku-pakuan, resam (Dicranopteris linearis), pakis (Stenochlaeua palustris), mahang (Macaranga pruinosa Muell.Arg), laban (Vitex pubescens), asam rawa, karet (Hevea brasinensis) and akasia (Acacia mangium). Ground storey vegetation and tree sapling stage were similar plant-type structures and compositions, while sapling and tree-level vegetation were completely different structure and composition of plant species in the two areas at ex-burnt in 2014 and 2009.Keywords : ex-burnt peatland, peat swamp forest, succesion